STATUS PERNIKAHAN DAN KEMAMPUAN IBU DALAM MENSTIMULASI PERKEMBANGAN PSIKOSOSIAL OTONOMI ANAK USIA 18 BULAN -3 TAHUN - Esti Widiani - (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2019)
Psychosocial development in the age range of 18 months to 3 years is autonomy versus doubt. This development can be achieved by providing good stimulation. The purpose of this study was to determine the relationship between marital status and the ability of mothers to provide stimulation. This study uses an observational design with a cross sectional approach. The study was conducted in Kemantren Village, Jabung District, Malang Regency. The technique used for sampling in this study was accidental sampling with a total sample of 168 respondents. The instrument used to measure maternal abilities is a modification of the HOME Toddler-Child Care Inventory. Analysis of the data used was spearman rank with the statistical results there was a significant relationship between marital status and the ability of mothers to stimulate psychosocial development of autonomy with a value of p = 0.029 (p <0.005). It is recommended that BKB (Bina Keluarga Balita) groups need to be held in each Posyandu as a service center and learning center for mothers about early detection and stimulation of development. Keywords: marital status, mother's ability to stimulate